2024
DOI: 10.3389/fendo.2024.1333778
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiota and therapy for obesity and type 2 diabetes

Luyao Zhang,
Pai Wang,
Juan Huang
et al.

Abstract: There has been a major increase in Type 2 diabetes and obesity in many countries, and this will lead to a global public health crisis, which not only impacts on the quality of life of individuals well but also places a substantial burden on healthcare systems and economies. Obesity is linked to not only to type 2 diabetes but also cardiovascular diseases, musculoskeletal disorders, and certain cancers, also resulting in increased medical costs and diminished quality of life. A number of studies have linked cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 156 publications
0
1
0
Order By: Relevance
“…Combined with recent studies, we found that there is a strong association between GM and obesity & T2DM. Regulating GM has a positive impact on the treatment of T2DM (8)(9)(10)(11). GM disorders are typical of patients with T2DM.…”
Section: Introductionmentioning
confidence: 99%
“…Combined with recent studies, we found that there is a strong association between GM and obesity & T2DM. Regulating GM has a positive impact on the treatment of T2DM (8)(9)(10)(11). GM disorders are typical of patients with T2DM.…”
Section: Introductionmentioning
confidence: 99%